2020
DOI: 10.15430/jcp.2020.25.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Cancerous Inhibitor of Protein Phosphatase 2A as a Molecular Marker for Aggressiveness and Survival in Oral Squamous Cell Carcinoma

Abstract: Cancerous inhibitor of protein phosphatase 2A (CIP2A) has been identified as one of the most commonly altered proteins in human cancers. It blocks the tumor-suppressive action of protein phosphatase 2A (PP2A) complex and enhances malignancy. Thirty-five patients with squamous cell carcinoma of the oral cavity underwent surgical resection of the tumor. CIP2A was assessed by quantitative real-time PCR in the resected tumor tissues and in their adjacent normal tissues. CIP2A was found to be overexpressed in all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Significantly elevated CIP2A expression has also been found in osteosarcoma, endometrioid adenocarcinoma and laryngeal carcinoma, in which CIP2A can promote the malignant biological behaviors of these tumor cells (35)(36)(37). Notably, CIP2A is highly expressed in OSCC tissues, and high CIP2A expression has been reported to be related to poor prognosis and short survival time (9,10). Our previous study indicated that CIP2A is implicated in the regulation of tumor angiogenesis (11).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Significantly elevated CIP2A expression has also been found in osteosarcoma, endometrioid adenocarcinoma and laryngeal carcinoma, in which CIP2A can promote the malignant biological behaviors of these tumor cells (35)(36)(37). Notably, CIP2A is highly expressed in OSCC tissues, and high CIP2A expression has been reported to be related to poor prognosis and short survival time (9,10). Our previous study indicated that CIP2A is implicated in the regulation of tumor angiogenesis (11).…”
Section: Discussionmentioning
confidence: 94%
“…Cancerous inhibitor of protein phosphatase 2A (CIP2A), originally named KIAA1524 or p90, has been reported to act as an oncogene by promoting tumor growth in several types of cancer, including bladder cancer, non-small cell lung cancer and colorectal cancer (6)(7)(8). Notably, CIP2A is also highly expressed in OSCC tissues, and high CIP2A expression is significantly related to poor prognosis and short survival time (9,10). A previous study indicated that CIP2A participates in the regulation of tumor angiogenesis (11), and downregulation of CIP2A has been shown to suppress the proliferation and vascularization of renal clear cell carcinoma cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…In HNSCC, PP2A inactivation largely occurs in a non-genomic way, by overexpression of specific cellular PP2A inhibitors [22][23][24][25][26][27]. Like that, overexpression of CIP2A (Cancerous inhibitor of PP2A) or SET (Suvar/Enhancer of zeste/Trithorax) correlates with poor patient survival, enhanced HNSCC cell survival and decreased cisplatin response [25,[28][29][30][31][32][33]. However, whether other PP2A inactivating mechanisms could be of clinical relevance in HNSCC etiology or therapy response, remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In HNSCC, PP2A inactivation largely occurs in a non-genomic way, by overexpression of specific cellular PP2A inhibitors (Gouttia et al, 2022;Junttila et al, 2007;Katz et al, 2010;Leopoldino et al, 2012;Patel et al, 2008;Ventelä et al, 2014). Like that, overexpression of CIP2A (Cancerous inhibitor of PP2A) or SET (Suvar/Enhancer of zeste/Trithorax) correlates with poor patient survival, enhanced HNSCC cell survival and decreased cisplatin response (Alzahrani et al, 2020;Böckelman et al, 2011;Leopoldino et al, 2012;Liu et al, 2014;Ouchida et al, 2019;Routila et al, 2016;Sobral et al, 2014). However, whether other PP2A inactivating mechanisms could be of clinical relevance in HNSCC etiology or therapy response, remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%